Investigation of Chicken Slaughterhouse Wastewater Treatment using Bleaching earth and Bentonite Clay - Muhammad Izzat Izuddin Ismail; Nik Normunira Mat Hassan; Anika Zafiah Mohd Rus (Progress in Engineering Application and Technology, 2022)
Chicken processing industry is one of the main poultry industries in the world. The industrialization of chicken processing industry has become well known. Due to the increasing of it, the wastewater from the poultry industry must be treated. In this study, the researcher investigates the wastewater from chicken’s slaughterhouse using bleaching earth and bentonite clay to determine the physical property and comparison between BOD and COD of chicken wastewater after bleaching earth and bentonite clay treatment according to DOE standard. Two types of method was used in this research.  The first method is filtration using bleaching earth and bentonite clay without magnetic stir hot plate. Preparation of wastewater in method 1 shows bleaching earth is more efficient rather than bentonite clay. This is because sample 4 shows the chicken wastewater changed to clear water and the smell of chicken blood also disappeared. Meanwhile the result for BOD is 16.87mg/L and COD is 67.48mg/L. While for the second method is using bleaching earth and bentonite clay with magnetic stir hot plate. The result is contrary with method 1. Method 2 shows bentonite clay is more efficient to get clear water. It shown in Sample 4. During the interval the BOD result is 15mg/L while COD is 60mg/L. Both method shows the result for BOD and COD is in between DOE standard. As conclusion, the chicken wastewater treatment successfully done by Using 2 method of clay with are bleaching earth and bentonite clay. Both clay allow the chicken wastewater turn colour into clear water. It can be alternative way to treat water and become useful for other application.